The Optimization of Qur'an Reading Accuracy through the Iqro Method at Ummul Yaqin TPQ, Sukajaya, Palembang City - Nilam Fitriah; Afifuddin Ahmad Robbani; Nurdiana Sari; Wakib Kurniawan (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Teaching young children to read the Qur'an is not an easy task, as it requires not only adequate knowledge but also an appropriate teaching method that can be effectively applied in the learning process. This study examines the implementation of the Iqro method in improving the quality of Qur'an reading at Ummul Yaqin TPQ. The focus of this research is on teachers' efforts to optimize the accuracy of makhraj (pronunciation) and tajwid through the use of Iqro textbooks volumes 1–6. This study employs a descriptive qualitative research design. Data were collected through interviews and direct observations during the learning process. The main issue addressed in this study is that many students still experience difficulties in reading the Qur'an correctly and fluently. In addition, support from competent and qualified teachers with expertise in Qur'an recitation is essential. The findings of this study are expected to provide recommendations for enhancing the effectiveness of Qur'an reading instruction at Ummul Yaqin TPQ. Consequently, children will be better equipped to master Qur'an reading skills accurately and correctly in accordance with the rules of tajwid, progressing from the beginner level to advanced proficiency.